ANALISIS PEMASARAN BIJI KEMIRI (Aleurites Mollucana (L.) Willd) DI DESA BAKUBAKULU KECAMATAN PALOLO KABUPATEN SIGI - Rura, Yulius; Umar, Syukur; Alam, Andi Sahri (Universitas Tadulako, 2014)
The forest product of non-timber is one of the forest resources, which is directly related to societies who live around the forest. The forest product of non-timber, such as candlenut can give or increase the revenue of people who live around the forest. Candlenut (Aleurites moluccana (L) Wild) is one of commodity that is potentially to be developed. This research aims to know the marketing channel of candlenut (A. moluccana (L) Wild) product and to help society in solving their problem; either development of their business or improvement their income from candlenut in Bakubakulu village, Palolo, Sigi regency. The collecting data techniques used in this research were sampling purposive and snowball sampling. The purpose sampling is a sample determining technique with certain consideration. The certain consideration criteria is the candlenut farmer in Bakubakulu area. The sample determination was 25% of the total population. The sample determining technique was done by snowball sampling technique; i.e. a sample determining technique, which is originally small amount and become large amount of sample later on. The results, there showed that are two marketing channels of candlenut in Bakubakulu. The first one is from farmers to a small collector to a big collector in Bakubakulu to a wholesaler in Mamuju regency, West Sulawesi. The second way is from farmers to a big collector in Bakubakulu to a wholesaler in Mamuju. The analysis of total marketing margin of candlenut in Bakubakulu is the same i.e. 6.97%. The results of efficiency analysis of the candlenut marketing in Bakubakulu are different for each channel. The efficiency of the first channel marketing is 1.12% and the second channel is 1.67%. Keywords: Marketing channel, candlenut, total margin, marketing efficiency level.